A qualitative exploration: life after the emergency services. Issue 2 (7th November 2016) - Bracken-Scally, Mairéad; McGilloway, Sinéad
Abstract : Purpose: Much has been written about the impact of emergency service work on personnel, but very little is known about the lives of personnel once they have retired. The purpose of this paper is to explore the experiences and assess the quality of life (QoL) of emergency service retirees (ESRs) and to ascertain the possible longer term effects of emergency service work. Design/methodology/approach: A series of one-to-one interviews was conducted with ESRs ( n =10). These were then transcribed and analysed using interpretative phenomenological analysis. Findings: A number of key emergent themes and associated sub-themes were identified from the analysis including: retirement as a major life change; potential impact of working role and unique aspects of emergency service work; trauma; and health and ageing more generally. Overall, the findings highlight the unique experiences of ESRs and the potential longer term impact of emergency service work on QoL in retirement. Originality/value: In an under-researched area, the findings point towards a need to improve the transition to retirement for ESRs and, in particular, to enhance available supports, information and guidance for retirees, both prior to and following retirement.